2023
DOI: 10.1186/s13054-023-04592-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in adult patients with status epilepticus: a seven-year two-center observation

Sira M. Baumann,
Pia De Stefano,
Paulina S. C. Kliem
et al.

Abstract: Background Conflicting findings exist regarding the influence of sex on the development, treatment, course, and outcome of status epilepticus (SE). Our study aimed to investigate sex-related disparities in adult SE patients, focusing on treatment, disease course, and outcome at two Swiss academic medical centers. Methods In this retrospective study, patients treated for SE at two Swiss academic care centers from Basel and Geneva from 2015 to 2021 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The cutoff of age with poor outcomes in our study was 36 years; however, the association was not significant [ 2 , 3 , 11 - 14 ]. While some studies have shown female gender being associated with unfavourable outcomes, the gender of our study patients did not show any significant correlation, although male patients were more in number than female patients [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 86%
“…The cutoff of age with poor outcomes in our study was 36 years; however, the association was not significant [ 2 , 3 , 11 - 14 ]. While some studies have shown female gender being associated with unfavourable outcomes, the gender of our study patients did not show any significant correlation, although male patients were more in number than female patients [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 86%
“…There is a growing body of evidence that critically ill women experience worse outcomes, especially after OHCA, even after adjusting for age and cardiac arrest circumstances 5 , 64 , 65 . Sex and/or gender differences in resource allocation, such as admission to intensive care, provision of coronary artery bypass grafting, mechanical ventilation, and targeted temperature management, were also observed in other critical care populations and might partially explain the observed differences 66 68 .…”
Section: Discussionmentioning
confidence: 93%
“…Differences in sex can affect disease presentation, symptom severity, drug metabolism, and response to treatment. A 2023 study examined sex disparities in a retrospective analysis of 762 cases of status epilepticus from two Swiss tertiary care centers revealed that women were more prone to focal nonconvulsive status epilepticus without coma, whereas men were more likely to experience status epilepticus with motor symptoms 79 . Moreover, the study investigated factors related to outcomes and found that women were less likely to be discharged home and more likely to be discharged to nursing homes or hospices.…”
Section: Discussionmentioning
confidence: 99%